Evaluation of the geographical utility of Eastern Russell's viper (Daboia siamensis) antivenom from Thailand and an assessment of its protective effects against venom-induced nephrotoxicity. - Janeyuth Chaisakul; Jaffer Alsolaiss; Mongkon Charoenpitakchai; Kulachet Wiwatwarayos; Nattapon Sookprasert; Robert A Harrison; Narongsak Chaiyabutr; Lawan Chanhome; Choo Hock Tan; Nicholas R Casewell (Public Library of Science (PLoS), 2019)
Background Daboia siamensis (Eastern Russell's viper) is a medically important snake species found widely distributed across Southeast Asia. Envenomings by this species can result in systemic coagulopathy, local tissue injury and/or renal failure. While administration of specific antivenom is an effective treatment for Russell's viper envenomings, the availability of, and access to, geographically-appropriate antivenom remains problematic in many rural areas. In this study, we determined the binding and neutralizing capability of antivenoms manufactured by the Thai Red Cross in Thailand against D. siamensis venoms from four geographical locales: Myanmar, Taiwan, China and Thailand. Methodology/principle findings The D. siamensis monovalent antivenom displayed extensive recognition and binding to proteins found in D. siamensis venom, irrespective of the geographical origin of those venoms. Similar immunological characteristics were observed with the Hemato Polyvalent antivenom, which also uses D. siamensis venom as an immunogen, but binding levels were dramatically reduced when using comparator monovalent antivenoms manufactured against different snake species. A similar pattern was observed when investigating neutralization of coagulopathy, with the procoagulant action of all four geographical venom variants neutralized by both the D. siamensis monovalent and the Hemato Polyvalent antivenoms, while the comparator monovalent antivenoms were ineffective. These in vitro findings translated into therapeutic efficacy in vivo, as the D. siamensis monovalent antivenom was found to effectively protect against the lethal effects of all four geographical venom variants preclinically. Assessments of in vivo nephrotoxicity revealed that D. siamensis venom (700 μg/kg) significantly increased plasma creatinine and blood urea nitrogen levels in anaesthetised rats. The intravenous administration of D. siamensis monovalent antivenom at three times higher than the recommended scaled therapeutic dose, prior to and 1 h after the injection of venom, resulted in reduced levels of markers of nephrotoxicity and prevented renal morphological changes, although lower doses had no therapeutic effect. Conclusions/significance This study highlights the potential broad geographical utility of the Thai D. siamensis monovalent antivenom for treating envenomings by the Eastern Russell's viper. However, only the early delivery of high antivenom doses appears to be capable of preventing venom-induced nephrotoxicity.